PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) DENGAN PENDEKATAN SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY (SETS) PADA POKOK BAHASAN ASAM BASA KELAS XI SMA/MA - Juniati, Tria; M. Noer, Asmadi; Susilawati, Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The aim of this research is to develop a Student Worksheet (SWs) with the SETS (Science, Environment, Technology and Society) Approach on the subject of Acid Bases. This type of research is research and development (R & D) with the Plomp development model which includes the initial investigation phase, design phase, realization / construction phase, test phase, evaluation and revision, and implementation phase. This research was conducted until the implementation in the form of one-on-one trials, trials limited to teachers and students. This research was conducted at FKIP Riau University, High School 2 Pekanbaru and Al-Azhar Syifa Budi Pekanbaru High School. The object of this research is SWs with SETS approach. The data analysis technique used in this study is descriptive statistical analysis, performed by calculating the score obtained at the time of validation. The assessment of the feasibility aspects of SWs by the validator team in the form of content eligibility, characteristics of the SETS approach, linguistic, presentation, and graphic characteristics had a score of 91.67%, 95.00%, 89.59%, 88.89%, and 89, respectively. 58%. So, overall the average score of acid-base SWs validation with the SETS approach is 90.95% included in the validity eligibility criteria, meaning that the developed SWs is feasible to be tested on a limited basis whereas the responses of teachers and students to SWs get a percentage of 97.32% and 86.06% are in good criteria.Keywords: Student WorkSheet (SWs), SETS Approach, acid and base